2022
DOI: 10.3390/rs14112534
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Textural and Spectral Information of UAV Hyperspectral Images for the Improved Estimation of Rice Aboveground Biomass

Abstract: The accurate and rapid estimation of the aboveground biomass (AGB) of rice is crucial to food security. Unmanned aerial vehicles (UAVs) mounted with hyperspectral sensors can obtain images of high spectral and spatial resolution in a quick and effective manner. Integrating UAV-based spatial and spectral information has substantial potential for improving crop AGB estimation. Hyperspectral remote-sensing data with more continuous reflectance information on ground objects provide more possibilities for band sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…These factors impose constraints on further advancements in monitoring accuracy. To address the issue of low accuracy in monitoring AGB based on spectral information, an increasing number of researchers are inclined toward utilizing texture features (TFs) to improve the precision of crop AGB monitoring ( Liu Y. et al., 2019 ; Yue et al., 2019 ; Wang F. et al., 2022 ; Xu T. et al., 2022 ). TFs describe the frequency of variations in attribute values among adjacent pixel pairs within a specific window ( Liu Y. et al., 2019 ; Yue et al., 2019 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These factors impose constraints on further advancements in monitoring accuracy. To address the issue of low accuracy in monitoring AGB based on spectral information, an increasing number of researchers are inclined toward utilizing texture features (TFs) to improve the precision of crop AGB monitoring ( Liu Y. et al., 2019 ; Yue et al., 2019 ; Wang F. et al., 2022 ; Xu T. et al., 2022 ). TFs describe the frequency of variations in attribute values among adjacent pixel pairs within a specific window ( Liu Y. et al., 2019 ; Yue et al., 2019 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This occurs because this band serves as the transition region between the infrared and near-infrared bands, where spectral reflectance transitions rapidly from a low negative correlation to a high positive correlation. This shift is attributed to strong absorption and reflection ( Kanke et al., 2016 ; Xu et al., 2022 ). The correlation between FD and AGB was generally greater than that between OS and SD at the different fertility stages ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, previous studies have typically employed multi-hill harvesting to acquire a single point of data when constructing the datasets required for the development of UAV-based growth estimation models 12,16,18,25 . This study has demonstrated the potential of utilizing single-hill datasets, which is an important finding for the labor-saving collection of ground-truth data in model development.…”
Section: Potentials and Limitations Of Labor-saving Single-hill Datasetmentioning
confidence: 99%
“…When we quantify the plant growth of a specific plot in a field experiment within the realm of crop science research, multiple hills are harvested within the plot and their average value is employed to obtain a representative value for the plot to account for growth variation occurring among hills within the plot 14 . In line with this, studies on growth estimation using UAV aerial imagery have conventionally collected ground measurements in a similar manner, for example, Zheng et al 15 collected AGB data based on the mean value of 20 randomly selected hills; Xu et al 16 obtained AGB data by harvesting four adjacent hills for each data point; Buscon et al 17 conducted AGB and LAI measurements by surveying four contiguous hills collectively; Yamaguchi et al 18 sampled eight neighboring hills to measure LAI and their average value was used to prepare datasets. However, when we focus on developing a growth estimation model using UAV photogrammetry, we can consider using data based on fewer harvested hills to save labor in ground measurement.…”
Section: Introductionmentioning
confidence: 99%